Síntese, caracterização e estudos biológicos envolvendo complexos de paládio(II) e rutênio(II) com hidrazidas e carbazatos - Sousa, Luana Munique (2016)
This work describes the synthesis, characterization and evaluation of the cytotoxic activity of new palladium(II) and ruthenium(II) complexes with hydrazides and carbazates. The complexes of type trans-[Pd(L)2Cl2], in which L = 4-methoxybenzylcarbazate (4-MC), benzyl carbazate (BC), 4-fluorophenoxyacetic acid hydrazide (4-FH), 3- methoxybenzyl hydrazide (3-MH), ethyl carbazate (EC) and tert-butylcarbazate (TC) were characterized by elemental analyses, conductivity measurements, TG/DTA, mass spectrometric, IR(ATR-FTIR) and NMR spectroscopy (solution and solid-state). In all reactions, were obtained square planar complexes with hydrazides or carbazates coordinated via NH2 groups. The cytotoxic activity of the compounds trans-[Pd(4-MC)2Cl2] (I) and trans-[Pd(4-FH)2Cl2] (III) was evaluated in a chronic myelogenous leukemia cell line and they showed poor activity. On the other hand, the complexes of the type fac-[RuCl2(S-dmso)3(L)], in which L = 4-methoxybenzylcarbazate (4-MC), benzyl carbazate (BC), 3,5-dimethoxy-α,α-dimethylbenzyl carbazate (DDC), 4-fluorophenoxyacetic acid hydrazide (4-FH), 3-methoxybenzyl hydrazide (3-MH) were characterized by IR (ATR-FTIR), UV-Vis, 1H NMR and elemental analysis. Furthermore, the structure of the complex fac-[RuCl2(S-DMSO)3(BC)] was determined by single-crystal X-ray diffraction, and as can see, the ruthenium ion has a distorted octahedral geometry and is coordinated to BC through the nitrogen atom from the NH2 group. Stability tests in buffer solution and DMSO indicated that after 24 hours the compound fac-[RuCl2(S-DMSO)3(4-FH)] loses a chloride ligand forming a cationic specie. The cytotoxic activity of ruthenium(II) complexes was evaluated in three tumor cell lines. However, the results indicate that the compounds are not active.